Pemberdayaan Ekonomi Kaum Difabel melalui Circular Economy Berbasis Komoditas Unggulan Daerah dan Kampanye Digital Inklusivitas - Hartono, Budi; Atmaja, Hanung Eka; Hardyta, Galy; Utomo, Brilian Setyo; Lutvi, Muhammad; Wardhani, Amelia Cyntia Kusuma (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Persons with disabilities often experience limited access to productive economic opportunities due to social stigma, inadequate skills, and weak systemic support. This community engagement program aims to strengthen economic and food self-reliance among persons with disabilities through a circular economy approach based on regionally superior commodities, supported by an inclusive digital campaign. A participatory–collaborative method was employed, encompassing local commodity identification, skills training in salak processing, maggot cultivation, Elba chicken–based urban farming, intensive mentoring, and digital outreach. The results demonstrate substantial improvements in participants’ capacities, particularly in maggot production skills (from 30% to 80%) and food self-sufficiency (from 20% to 60%), alongside increased public awareness of the economic potential of persons with disabilities. Although the digital campaign remains at an initial dissemination stage, the program exhibits strong sustainability potential in promoting inclusive, locally grounded economic empowerment.